The Effect of Butorphanol on the Mean Arterial Blood Pressure of Laboring Women With Hypertension [8L]. (May 2016) - Seah, Angeline; Chappelle, Joseph
Abstract : INTRODUCTION: Many women receive butorphanol during labor. The American College of Obstetricians and Gynecology state that butorphanol may increase blood pressure levels and should be avoided in patients with chronic hypertension or preeclampsia. The objective of this study is to evaluate whether there is a significant change in Mean arterial blood pressures (MAP) after butorphanol administration. METHODS: MAPs were compared between women with and without hypertensive disorders in labor pre and post butorphanol administration between January 2010 and December 2012. Independent t test assessed for differences between MAP in women with HTN disorders and those who did not. RESULTS: 154 women were included with 77 in each group. The women in the hypertensive group were significantly delivered at a younger gestational age ( P <.003) and found to have a larger BMI ( P <.0015). There was no statistical difference in race, parity, or mode of delivery between the two groups. Women in the hypertensive group had significantly elevated blood pressures as compared to the normotensive group at all study intervals ( P <.001). The blood pressure decreased at the 1 hour mark after administration in the hypertensive group ( P =.02) but there was no statistically significant difference between the pre and post administration MAPs at any of the other time intervals studied in either group. CONCLUSION: There is no increase in mean arterial blood pressure after butorphanol administration in laboring pregnant women. Butorphanol is a safe analgesic choice for women with and without hypertensive disorders.